Lactic Acid Bacteria May Impact Intestinal Barrier Function by Modulating Goblet Cells - Ren, Chengcheng (Mol Nutr Food Res, 2018)
SCOPE: Lactic acid bacteria (LAB) are recognized to promote gastrointestinal health by mechanisms that are not fully understood. LABs might modulate the mucus and thereby enhance intestinal barrier function. Herein, we investigate effects of different LAB strains and species on goblet cell genes involved in mucus synthesis. METHODS AND RESULTS: Gene expression profiles of goblet‐cell‐associated products (mucin MUC2, trefoil factor 3, resistin‐like molecule β, carbohydrate sulfotransferase 5, and galactose‐3‐O‐sulfotransferase 2) induced by LAB or their derived conditioned medium in human goblet cell line LS174T are studied. Effects of LAB on gene transcription are assessed with or without exposure to TNF‐α, IL‐13, or the mucus damaging agent tunicamycin. LAB do impact the related genes in a species‐ and strain‐specific fashion and their effects are different in the presence of the cytokines and tunicamycin. Bioactive factors secreted by some strains are also found to regulate goblet cell‐related genes. CONCLUSION: Our findings provide novel insights in differences in modulatory efficacy on mucus genes between LAB species and strains. This study further unravels direct interactions between LAB and intestinal goblet cells, and highlights the importance of rationally selecting appropriate LAB candidates to achieve specific benefits in the gut.